برصغیر کے مرتدین: تاریخی تناظرمیں تحقیقی جائزہ: Apostates of the Subcontinent: A Research Review in the Historical Perspective - Dr. Syed Toqeer Abbas; Dr. Saeed Ur Rahman; Nabeela Shams (Al Manhal Research Journal, 2024)
The Islamic World faces numerous issues these days, such as a lack of intellectual cohesion, partiality, sectarian unrest, economic decline, a lack of political centralization, a lack of knowledge about religious sciences, a lack of interest in contemporary sciences, etc. No awareness or paying no attention to these issues is another difficulty. In addition to these issues, the younger generation is becoming more and more apostasy-oriented. This is a matter that all Muslim nations are dealing with. The Subcontinent's Muslims are likewise affected by this issue. Following the British domination of India, Muslims began to convert to other religions rapidly. Initially, the majority of Muslims were converted to Christianity; however, throughout time, they also began to accept Hinduism, and currently, a large number of Muslims are becoming atheists as a result of advancements in science. Perhaps there wouldn't have been as much loss if these Muslims had simply abandoned Islam, but instead of doing so, they practically became enemies of Islam. Among them, some apostates produced books, some founded study centers, and still others founded worldwide nongovernmental organizations (NGOs) to offer other apostates every convenience. To make the readers aware of the actions of some of these apostates, this short article provides a brief introduction to them.